Little room for maneuver: Belgium assumes OSCE chairmanship - Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2006)
Belgium took over the rotating chairmanship of the Organization for Security and Cooperation in Europe (OSCE) on January 1. In the coming twelve months it will now be up to Foreign Minister Karel de Gucht to restore consensus on the OSCE's institutional structure and remit, which seems to have crumbled in recent months. Major differences between member states overshadowed the 30th anniversary of the CSCE process in August 2005 and the annual meeting of the Ministerial Council in December 2005 in the Slovenian capital Ljubljana. The three most contentious areas of policy, and consequentially the greatest challenges for the Belgian chairmanship, are the process of internal reform of the OSCE, observance of promises made by members in the field of conflict resolution, and the future of the OSCE election monitoring missions. (SWP-Comments / SWP)
Keywords: 320